Pengaruh Banjir terhadap Adaptasi Rumah Tinggal di Warungboto, Yogyakarta - Kristiyani, Wahyu Desy; Bawole, Paulus; Damanik, Imelda Irmawati (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2025)
Title: The Impact of Floods on Residential Adaptation in Warungboto, Yogyakarta Settlements around the riverbank are not free from the threat of flooding due to overflowing river water. To reduce this risk, the community tries to adapt to their homes. This research aims to determine the influence of flooding on the adaptation of residential houses in Warungboto, Yogyakarta. The method used is a descriptive qualitative with observation, interview, and documentation techniques from both Warungboto residents and the author by analyzing homes using morphological, physiological, and cultural adaptation theories. The results found were that all types of adaptation were carried out by flood victims and were influenced by the location of the house, the status of the house, and the length of stay. Floods affect the adaptation of a residence by changing the house's orientation, adding water-retaining partitions, changing the house plan, and adding new rooms at a higher level than the ground floor.